Boron Nitride‐supported Sub‐nanometer Pd6 Clusters for Formic Acid Decomposition: A DFT Study. Issue 9 (25th April 2017) - Schimmenti, Roberto; Cortese, Remedios; Duca, Dario; Mavrikakis, Manos
Abstract: A periodic, self‐consistent planewave DFT study was carried out to explore the potential use of Pd6 clusters supported on a boron nitride sheet as a catalyst for the selective decomposition of formic acid (HCOOH) to CO2 and H2 . The competition between formate (HCOO) and carboxyl (COOH) paths on catalytic sites, with different proximities to the support, was studied. Based on energetics alone, the reaction may mainly follow the HCOO route. Slightly lower activation energies were found at the lateral sites of the cluster as compared to top face sites. This is particularly true for the bidentate to monodentate HCOO conversion. Through comparison of results with similar studies on HCOOH decomposition on extended Pd surfaces, it was demonstrated that the existence of undercoordinated sites in the sub‐nanometer cluster could play a key role in preferentially stabilizing HCOO over COOH, which is a common CO precursor in this reaction. A hydrogen spillover mechanism was also investigated; migration toward the boron nitride support is not favorable, at least in the early stages of the reaction. However, hydrogen diffusion on the cluster has low barriers compared to those involved in formic acid decomposition. Abstract : Sub‐nano key : Density functional theory calculations offer atomistic insights into the catalytic activity of a Pd6 sub‐nanometer cluster, supported on a boron nitride sheet, for formic acid decomposition. Undercoordination of the cluster sites may be a key factor for avoiding CO production and poisoning.